2021
DOI: 10.1016/j.bioactmat.2020.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Nanomotor-based adsorbent for blood Lead(II) removal in vitro and in pig models

Abstract: Blood lead (Pb(II)) removal is very important but challenging. The main difficulty of blood Pb(II) removal currently lies in the fact that blood Pb(II) is mainly complexed with hemoglobin (Hb) inside the red blood cells (RBCs). Traditional blood Pb(II) removers are mostly passive particles that do not have the motion ability, thus the efficiency of the contact between the adsorbent and the Pb(II)-contaminated Hb is relatively low. Herein, a kind of magnetic nanomotor adsorbent with movement ability under alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 82 publications
(79 reference statements)
0
15
0
1
Order By: Relevance
“…After 2 h of incubation, all samples were centrifuged, and the absorption of the resulting supernatants was measured at 561 nm. From the absorption results, we estimated the hemolysis percentage using following equation: Hemolysis rate = [(OD samples – OD negative )/(OD positive – OD negative ) × 100%] [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…After 2 h of incubation, all samples were centrifuged, and the absorption of the resulting supernatants was measured at 561 nm. From the absorption results, we estimated the hemolysis percentage using following equation: Hemolysis rate = [(OD samples – OD negative )/(OD positive – OD negative ) × 100%] [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Micro/nanomotors (MNMs) have attracted great research interest in the past decade due to their promising applications in various fields, including biomedicine, microsensing, and environmental remediation. Among these applications, environmental remediation has attracted great interest. Due to the enhanced mass transfer and microcontact of the motors with the pollutants benefited from the locomotion and the flow-induced mixing, traditional diffusion-limited wastewater treatment can be accelerated by over one order of magnitude with the help of MNMs. , Various strategies have been proposed for the removal of contaminants, such as heavy metal ions, organic dyes, , oils, microorganisms, and even microplastics . Recently, it has been reported that the collective behavior of micromotors may offer the best solution for high-efficiency environmental remediation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the enhanced mass transfer and microcontact of the motors with the pollutants benefited from the locomotion and the flow-induced mixing, traditional diffusion-limited wastewater treatment can be accelerated by over one order of magnitude with the help of MNMs. 7,8 Various strategies have been proposed for the removal of contaminants, such as heavy metal ions, 9 organic dyes, 10,11 oils, 12 microorganisms, 13 and even microplastics. 14 Recently, it has been reported that the collective behavior of micromotors may offer the best solution for high-efficiency environmental remediation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the stability of lead in the bones, this dynamic balance often takes a long time, and with the current biomedical technology, it is difficult to remove the lead that exists in the bones and soft tissues. Therefore, it is of great significance to study the removal of Pb­(II) from blood. , However, blood Pb­(II) is mainly located inside red blood cells (RBCs) and binds to hemoglobin (Hb) (>95%), so it is very difficult to remove trace Pb­(II) from blood.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great significance to study the removal of Pb(II) from blood. 6,7 However, blood Pb(II) is mainly located inside red blood cells (RBCs) and binds to hemoglobin (Hb) (>95%), 8 so it is very difficult to remove trace Pb(II) from blood.…”
Section: ■ Introductionmentioning
confidence: 99%